The Effect of Accompanying Listening Teaching Activities and Previous Achievement in Arabic on the Development of Imagination of Sixth Graders - Nuser, Hamdan (Jordan Journal of Educational Sciences, 2009)
This study aimed at exploring the effect of accompanying listening teaching activities in Arabic lessons on the development of the learners' imagination. The study sample consisted of 59 sixth grade male students in two groups chosen randomly from the Yarmouk University Model School. The experimental group received instruction of listening skills using drawing, kinetic representation and cognitive activities. The control group received post-listening instruction in the conventional method by answering the after listening text questions included in the textbook . The experiment was conducted for 10 weeks in the 2nd semester 2008. To measure the effect of the experiment, the researcher used a three- part test which measured the dimensions of the imaginative ability of children, the first part of the test aimed at assessing the drawing effect on the development of the learners imagination; the second aimed at developing the cognitive responses; and the third part focused on the effect of kinetic representation on the learners' imagination while listening to the teacher. The test was administered before and after the experiment. The reliability of the test was calculated by test retest and found to be 0.82 for the 1st part (drawing), 0.85 for the second part (cognitive response) and 0.74 for the kinetic representation activities comprising a total 0.87. It was found that there were significant statistical differences at (0.05=α) in favor of the experimental group on the three dimensions. Besides, it was found that there was no interaction between the tested teaching activities and the students’ previous achievement levels in Arabic subject concerning the imaginative ability, which indicates that all students benefited from the teaching of the listening activities regardless of their previous different levels.